MiRNA Signatures Related to Invasiveness and Recurrence in Patients With Non-Functioning Pituitary Neuroendocrine Tumors - Nikolova, Emiliya; Nankova, Anelia; Kalenderova, Silvia; Georgieva, Bilyana; Hadzhiyanev, Asen; Bichev, Stoyan; Savov, Alexey; Todorova, Albena; Mitev, Vanyo; Elenkova, Atanaska (Experimental and Clinical Endocrinology & Diabetes, 2024)
Purpose: This preliminary study aimed to analyze and identify differentially expressed miRNAs in Bulgarian patients with non-functioning pituitary neuroendocrine tumors (NFPitNET). The relationship between deregulated miRNAs and tumor invasiveness, recurrence, and size was determined.Methods: Twenty patients with NFPitNET were selected and fresh pituitary tumor tissues were collected. RNA containing miRNAs were isolated using miRNAeasy mini kit and analyzed by quantitative real-time polymerase chain reaction (PCR) using LNA miRNA Cancer-Focus PCR Panel (Qiagen).Results: Three miRNAs (miR-210-3p, miR-149-3p, and miR-29b-3p) were deregulated in invasive compared to non-invasive NFPitNETs. Differential expression of four-miRNA signatures – miRNA-17, miR-19, miR-106a, and miR-20, correlated with patient recurrence.Conclusion: This prospective pilot study selected a unique miRNA expression profile, that correlates with invasiveness and recurrence in non-functioning pituitary neuroendocrine tumors. Moreover, some of the selected miRNAs are reported for the first time in patients with this disease, shedding light on the molecular mechanisms involved in pituitary pathogenesis. The identified miRNAs demonstrate potential as biomarkers, deserving further investigation in a larger cohort to validate their clinical applicability.
Keywords: miRNA; non-functioning pituitary neuroendocrine tumors; invasion; recurrence